System of Zemstvo Elections According to Regulations on Zemstvo Institutions of 1890 in Estimates of Russian Periodicals - A. A. Sorokin; M. V. Medovarov (Научный диалог, 2021)
The article is devoted to the little-studied issue of the reaction of the Russian periodicals to changes in the zemstvo electoral legislation in accordance with the Regulations on zemstvo institutions in 1890. The positions of the leading conservative (“Moskovskie vedomosti”, “Grazhdanin”, “Russian Review”, “Russian Bulletin”, “Novoye Vremya”), liberal (“Novosti”, “Nedelya”, “Bulletin of Europe”, “Russian Thought”, “Russkie vedomosti”, “Sudebnaya Gazeta”) and populist (“Russian wealth”, “Novoye Slovo”, “Severny Vestnik”) editions. The attitude of periodicals to key changes in the system of zemstvo elections is shown: the establishment of estate electoral meetings, the privileged position of the nobility, a change in the order of representation from peasants, the deprivation of voting rights for Jews, a change in the procedure for approving members and chairmen of zemstvo councils. The authors argue that certain provisions of the new electoral law did not suit both conservative and liberal and populist publications. At the same time, there was no single approach within each of these groups. Some conservative publications in their proposals and criticism were close to the liberal ones (“Novoye Vremya”), and vice versa (“Novosti”, “Nedelya”). In general, each of the editions focused mainly on individual changes, criticizing or supporting them, as well as proposing their own versions of their changes.